Lectotypification, synonymy, and a new name in Senna series Aphyllae (Leguminosae: Caesalpinioideae) - Robbiati, Federico; Ariza, Luis; Anton, Ana; Fortunato, Renee (Phytotaxa, 2014)
In series Aphyllae, Senna acanthoclada is lectotypified on images, housed at Albrecht von Haller Institute of Plant Sciences, Universität Göttingen; a new circumscription and synonyms for S. aphylla are given, and a new name: S. aphylla var. pedula var. nov. is proposed.